Oral Health Messiers: Diabetes Mellitus Relevance - Ahmad R (Dove Medical Press, 2021)
Rahnuma Ahmad,1 Mainul Haque2 1Department of Physiology, Medical College for Women and Hospital, Dhaka, Bangladesh; 2The Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur, 57000, MalaysiaCorrespondence: Mainul HaqueThe Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kem Perdana Sungai Besi, Kuala Lumpur, 57000, MalaysiaEmail runurono@gmail.comAbstract: This article aims to narrate the various oral complications in individuals suffering from diabetes mellitus. Google search for “diabetes mellitus and oral complications” was done. The search was also carried out for “diabetes mellitus” and its oral complications individually. Diabetes mellitus is a chronic metabolic disorder that is a global epidemic and a common cause of morbidity and mortality in the world today. Currently, there are about 422 million cases of diabetes mellitus worldwide. Diabetic patients can develop different complications in the body such as retinopathy, neuropathy, nephropathy, cardiovascular disease. Complications in the oral cavity have been observed in individuals suffering from diabetes mellitus. A study noted that more than 90% of diabetic patients suffered from oral complications. Another research has shown a greater prevalence of oral mucosal disorders in patients with diabetes mellitus than non-diabetic population: 45– 88% in patients with type 2 diabetes compared to 38.3– 45% in non-diabetic subjects and 44.7% in type 1 diabetic individuals compared to 25% in the non-diabetic population. Oral complications in people with diabetes are periodontal disease, dental caries, oral infections, salivary dysfunction, taste dysfunction, delayed wound healing, tongue abnormalities, halitosis, and lichen planus. The high glucose level in saliva, poor neutrophil function, neuropathy, and small vessel damage contribute to oral complications in individuals with uncontrolled diabetes. Good oral health is imperative for healthy living. Oral complications cause deterioration to the quality of life in diabetic patients. Complications like periodontal disease having a bidirectional relationship with diabetes mellitus even contribute to increased blood glucose levels in people with diabetes. This article intends to promote awareness regarding the oral health of diabetics and to stress the importance of maintaining proper oral hygiene, taking preventive measures, early detection, and appropriate management of oral complications of these patients through a multidisciplinary approach.Keywords: diabetes mellitus, hyperglycemia, oral complications, periodontal disease, salivary dysfunction, dental caries, infection, awareness, multidisciplinary approach